Research on Method in Measurement and Parameter of Energy Saving for WLAN Access Point - Bo Gao; Fei Wu; Rui Lin; Chengbin Shen (Dianxin kexue)
As the fast growing of WLAN's access point（AP）, reducing power consumption of large amount of AP became an important issue in telecommunication industry. Many similar products test methods and standards in power consumption area which proposed by different nations and organizations were referred. The evaluation method and requirement dictator of AP power consumption were researched. A timing weighted method was used to module the power consumption of the AP. In addition, this research method was used to test quantities equipment under different types and working status of existing network equipment, the advice of energy saving was provided.